Airbnb Host Responsibilities and Community Resilience: The case of Japan - Kaniadakis, Antonios; Hayakawa, Chiga; Farmaki, Anna (My University, 2022)
In Japan, the shortage of accommodation facilities has become a concern due to the increasing number of tourists. In light of the 2020 Olympic and Paralympic Games (moved to 2021 due to the coronavirus disease 2019 (COVID-19) pandemic), this problem is likely to escalate and raises the need for the authorities to deal with the temporary influx of tourists. Private lodging emerges as a possible solution to this problem and also as a way to revitalize regions and repopulate vacant houses. Considering the Private Lodging Business Act recently established in Japan, this chapter explores Airbnb hosts’ perceptions of their responsibilities. This leads to an increase in our understanding of the associated implications of these hosts’ practice on the resilience of the local community. Drawing from semi-structured interviews with 16 Japanese hosts, we reveal insights on hosts’ perceived responsibilities in the peer-to-peer accommodation context and how hosts and platforms can contribute to community resilience.
Keywords: Airbnb; Host; Japan; Resilience; Responsibility; Community